KOMUNIKASI ORGANISASI (ANALISISPENDEKATAN MIKRO) DALAM PELAKSANAAN REBOISASI PADA KESATUAN PENGELOLA HUTAN PRODUKSI (KPHP) MODEL PULAU LAUT DAN SEBUKU - Junet Usodo; Ma'ruf Abdullah; Zain Noktah Aslie (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Research is one of the objectives of to overcome problem in a organization on this research writer set some limits trouble is as follows: corrupt communication organization that occurs in units of unity of production forest management (KPHP) model sea island and sebuku, and approach micro to organizations especially approach among members organization in the implementation of the reforestation in units of unity of production forest management (KPHP) model sea island and sebuku especially on the implementation of reforestation.The results of the study found that communicate and coordinate with stakeholders to to institutional strengthening so that the implementation of reforestation possible consistent with the objectives of to be achieved.Keywords: Organizational communications, Reboisation, forest production management